THE POWER RELATIONS BETWEEN THE DRUG TRAFFICKERS AND THE GOVERNMENT: A CASE STUDY IN MEXICO - , Antonia Rahayu Rosaria Wibowo, Drs. Dafri Agussalim, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Drug trafficking is famous in Mexico. It happens because Mexico involves in the production, distribution, and consumption of the drugs. This condition attracts government's attention because drug trafficking bring many criminal activities in Mexico. Because of that reason, government wants to abolish drug trafficking business. However, the relation between the drug traffickers and the goverment in Mexico is not always an opposed relationship. In some times, they have a beneficial relationship when they work together to get the same purpose. There are two questions that must be answered in this thesis. The first questions is why and how do the power relations happen in Mexico between the drug traffickers and the goverment? The second question is what are the impacts of the two types of power relations? Drug trafficking has existed for a long time in Mexico, but it gets its important point in 1980s and 1990s. Along its development, Mexico has seven major cartels now. Drug trafficking network is possible because of the quality of the means of transportation, the local gangs, the laboratory to produce the drugs, and the route of drug trafficking. For improving their business, drug traffickers need to be powerfull. The sources of their power are the demand from the consumer, the high technology, and the gangs.